2000
DOI: 10.1002/1096-9098(200005)74:1<41::aid-jso10>3.0.co;2-r
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of peritoneal carcinomatosis with intent to cure

Abstract: After a learning curve of 18 months, the feasibility of the integrated treatment increased to greater than 90%, and mortality dramatically decreased. The combined treatment resulted in a high survival rate in patients with extensive carcinomatosis who were no longer responsive to traditional therapies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0
3

Year Published

2001
2001
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(37 citation statements)
references
References 9 publications
1
32
0
3
Order By: Relevance
“…Elias et al 9 concluded from their experience in Paris that a 50% 2-year survival could be reached, and the group of Beaujard 22 in Lyon found a median survival of 16 months in patients who underwent successful cytoreduction. The Roman study of Cavaliere et al 23 showed a 2-year survival of 61%. At The Netherlands Cancer Institute, a median survival of 22 months was found in a randomized trial comparing cytoreduction plus HIPEC followed by systemic adjuvant chemotherapy with palliative surgery and systemic chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Elias et al 9 concluded from their experience in Paris that a 50% 2-year survival could be reached, and the group of Beaujard 22 in Lyon found a median survival of 16 months in patients who underwent successful cytoreduction. The Roman study of Cavaliere et al 23 showed a 2-year survival of 61%. At The Netherlands Cancer Institute, a median survival of 22 months was found in a randomized trial comparing cytoreduction plus HIPEC followed by systemic adjuvant chemotherapy with palliative surgery and systemic chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…The HIPEC chemotherapy used, temperature and duration was described in all 37 studies (eTable 2). The most commonly used HIPEC chemotherapy was cisplatin (CDDP) that was used either alone [26,42,49,50,55], or in combination with other agents such as doxorubicin [36,37,41,45,56], paclitaxel [40] or mitomycin-C [34,57] Figure 1). Only one study reached median overall survival for CRS with and without HIPEC (64.4 months and 46.4, respectively).…”
Section: Study Characteristicsmentioning
confidence: 95%
“…The first was published by Cavaliere et al [93] reporting about 20 patients with recurrent EOC. They reported a median OS of 25 mo with a 3-year survival of 50%.…”
Section: Peritoneal Carcinomatosis From Ovarian Cancermentioning
confidence: 99%